Electron tunneling between vibrating atoms in a copper nano-filament - Mohammad Al-Mamun (Nature Portfolio, 2021)
Abstract Nanowires, atomic point contacts, and chains of atoms are one-dimensional nanostructures, which display size-dependent quantum effects in electrical and thermal conductivity. In this work a Cu nanofilament of a defined resistance and formed between a Cu and Pt electrode is heated remotely in a controlled way. Depending on the robustness of the conductive filament and the amount of heat transferred several resistance-changing effects are observed. In case of sufficiently fragile nanofilament exhibiting electrical quantum conductance effects and moderate heating applied to it, a dramatic increase of resistance is observed just after the completion of the heating cycle. However, when the filament is allowed to cool off, a spontaneous restoration of the originally set resistance of the filament is observed within less than couple tens of seconds. When the filament is sufficiently fragile or the heating too excessive, the filament is permanently ruptured, resulting in a high resistance of the cell. In contrast, for robust, low resistance filaments, the remote heating does not affect the resistance. The spontaneous restoration of the initial resistance value is explained by electron tunneling between neighboring vibrating Cu atoms. As the vibrations of the Cu atoms subside during the cooling off period, the electron tunneling between the Cu atoms becomes more likely. At elevated temperatures, the average tunneling distance increases, leading to a sharp decrease of the tunneling probability and, consequently, to a sharp increase in transient resistance.